PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENUMBUHKAN NILAI-NILAI KARAKTER PESERTA DIDIK MELALUI PROGRAM PEMBIASAAN SHALAT SUNNAH DHUHA DI SMP ISTIQOMAH - Aja Rowikarim (HASBUNA : Jurnal Pendidikan Islam, 2023)
The purpose of this study is to find out: First, to find out how the role of the PAI teacher is in cultivating the Character Values ​​of Students at Istiqomah Middle School. Second, to find out how the Sunnah Dhuha Prayer Habituation Program at Istiqomah Middle School is. Third, to find out what are the supporting and inhibiting factors of the role of the PAI teacher in cultivating the Character Values ​​of Students Through the Dhuha Circumcision Prayer at Istiqomah Middle School. The type of research used is qualitative research. Sources of data in the study were teachers and students. The research instruments used were observation guidelines, interview guidelines, documentation. Data analysis techniques used are data reduction techniques, data presentation, data verification.The results of the research can be summarized as follows: The role of the PAI teacher in cultivating Student Character Values ​​at Istiqomah Middle School plays a very important role in helping the development of Students to realize their life goals optimally, namely through the Dhuha prayer habituation program the character values ​​of students can be formed. Which is where the Duha prayer at the Istiqomah Middle School is carried out in the morning before class starts.